Virtual Workshop on Antibiotic Use and Resistance for Malaysian Secondary School Students - Leong, Jasmine Shi Qi; Tan, Sui Ling Janet; Madhavan, Priya; Hamzah, Sharina; Rahim, Nusaibah Abdul; Yow, Hui Yin (Indian Journal of Pharmaceutical Education and Research)
Background: Antibiotic-resistant infections, which cause significant global morbidity and mortality, are exacerbated by inadequate knowledge about antibiotic use, highlighting the need for improved education to prevent resistance. The e-Bug educational workshop potentially mitigates the global threat of Antibiotic Resistance (ABR). Aim: This study evaluated the effectiveness of the virtual e-Bug workshop on antibiotic Awareness and Knowledge, and Practice (AKP) among Malaysian secondary school students. Materials and Methods: The e-Bug workshop was conducted over 1 hr with four educational videos with Form 4 (Science stream) students from a national-type secondary school in Malacca, Malaysia. In pre- and post-workshop, a validated 20-AKP-items questionnaire was distributed. Results: Among 65 students involved in this study, the pre-workshop practice score was positive with a median (M) score of 67% and Interquartile Range (IQR) of 37.5. Awareness (M: 60%, IQR: 25) and knowledge (M: 50%, IQR: 17) were recorded as moderate. Following the e-Bug workshop, both awareness (M: 80%, IQR: 20) and knowledge (M:100%, IQR: 0) increased significantly (p<0.001). Conclusion: The e-Bug workshop is an effective tool to enhance students’ AKP on antibiotic use and resistance. This promises great scope for the design and implementation of future workshops and seminars.
Keywords: Antibiotic resistance; Awareness; Educational workshop; Knowledge; Practice.